Manutenção prescrita e manutenção real: uma abordagem baseada na atividade dos profissionais: o caso de uma indústria automobilística - Carvalho, Alex Luis de (Universidade Federal de São Carlos, 2011)
This study aims to present the determinants of activity in real situations, characterized by variability and unpredictability inherent in production systems, as well as understanding and relevance of the requirements developed with the effective participation of professionals. With this purpose, we studied the activities of professionals (mechanics and electricians) from a maintenance area of an automotive industry in two real situations of intervention, an corrective and other preventive. Based on the methodological assumptions of Ergonomic Work Analysis (EWA), as well as techniques of data collection, the real activity performed was faced with a prescription, showing many sources of variability, constraints and unexpected that are managed by professionals during the course of action mobilizing tacit skills, strategies for control of situations and actions not always conscious, which ensures really effective commitment between production and safety. The study results indicate that these prescriptions even tough developed with the effective participation of professionals, are inefficient for the live activity, showing how invisible it is their job to maintenance management, risks, project engineering and themselves. This finding was scrutinized in the discussion of the dissertation, aiming to the needs of acknowledgement and understanding of human live activity by all the organizations and professionals themselves so the importance of reflection on the events experienced in runtime. Finally, some proposals were suggested for changing the point of view and to reflect on the difficulties faced taking into account the perspective of a maintainer in the course of action focusing on considering the importance of the "during" and not just the "results" providing improvements to both company by increasing the reliability of facilities and for the professionals preserving their health and ensure their ability to work in the face of unforeseen circumstances and difficulties inherent in the process.
Keywords: Ergonomia; Atividade de manutenção; Profissionais de manutenção; Trabalho - instruções; Indústria automobilística; Análise Ergonômica do Trabalho (AET); Prescrições; Activity of maintenance; Maintenance professionals; Ergonomic Work Analysis (EWA); Prescriptions; Automotive industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO